Direct water treatment by APGD with rotating electrodes - Golota, V.; Mohanty, P.; Zavada, L. (Problems of Atomic Science and Technology, 2023)
The APGD with rotating star-shaped electrodes was applied directly to the surface of liquid as a counter electrode. It was shown that the rotation of electrodes enables the stabilization of the discharged. A high concentration of H₂O₂ and nitrates were measured. The high level of microbial reduction was shown for inoculated deionized water treated by APGD with rotating electrodes.